Hip adduction and abduction strength profiles in elite and sub-elite female soccer players according to players level and leg limb-dominance - Jaenada-Carrilero, E.; Vicente-Mampel, J.; Baraja-Vegas, L.; Thorborg, K.; Valero-Merlos, E.; Blanco-Gímenez, P.; Gargallo, P.; Bautista, I. J. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background Understanding the hip adduction and abduction strength in female soccer players is crucial for performance enhancement and injury prevention. This study compares the strength profiles in these muscle groups between elite and sub-elite female soccer players and assesses the impact of leg limb-dominance.